Geopolitics on the agenda: Genesis and evolution of the theme "territories and borders" - Fonseca, Valter Machado da (Seven Editora, 2023)
This essay aims to problematize the concepts of Territories and Borders. It inquires about past times, pointing to the primary origins of the social organizations of men who gather fruit, roots and hunters, nomads and their relationship with geographic space. The text discusses the evolution of techniques and how they impacted the organization of the territory and the construction of borders. The text uses a qualitative methodology based on an analytical and exploratory investigation with a view to investigating the evolution of space configuration as a function of the evolution of technologies. In view of this, he argues about the relationships between territories and borders with the new socio-spatial configurations derived from the new mobilities of volatile and speculative capital, forming economic power blocs and impacting borders and territories. It is concluded, to this extent, that territorial conflicts give new dynamics to the circulation of goods and, at the same time, make borders more selective obstacles to the migration of people and more open to the circulation of goods, thus impacting the entire circulation of the chain of goods originating from the capitalist productive chain, providing new forms of creation of added value and the expanded reproduction of capital. DOI:https://doi.org/10.56238/chaandieducasc-022